Quantification of Leishmania infantumDNA in the bone marrow, lymph node and spleen of dogs - Ramos,Rafael Antonio Nascimento (2013)
The aim of the present study was to quantify the parasite load ofLeishmania infantum in dogs using real-time PCR (qPCR). Bone marrow, lymph node and spleen samples were taken from 24 dogs serologically positive for L. infantum that had been put down by the official epidemiological surveillance service. According to the clinical signs the dogs were classified as asymptomatic or symptomatic. After DNA extraction, the samples were subjected to qPCR to detect and quantify L. infantum DNA. Out of the 24 dogs, 12.5% (3/24) were classified as asymptomatic and 87.5% (21/24) as symptomatic. Real-time PCR detected L. infantum DNA in all the animals, in at least one biological sample. In particular, 100% of bone marrow and lymph node scored positive, whereas in spleen, the presence of DNA was detected in 95.9% (23/24). In addition, out of 24 animals, 15 were microscopically positive to amastigote forms of L. infantum in bone marrow. No statistical significant difference was found in the overall mean quantity of DNA among the different biological samples (P = 0.518). Considering each organ separately, there was 100% positivity in bone marrow and lymph nodes, while among the spleen samples, 95.9% (23/24) were positive. Regarding the different clinical groups, the overall mean parasite load varied significantly (P = 0.022). According to the results obtained, it was not possible determine which biological sample was most suitable tissue for the diagnosis, based only on the parasite load. Therefore, other characteristics such as convenience and easily of obtaining samples should be taken into consideration.